The Influence of Salary, Incentives, Work Environment on Job Satisfaction in the Finance Division at PT TIP TOP Pondok Gede - Kurniawan, Robby; Cahaya, Yohanes Ferry (Dinasti Publisher, 2025)
This study aims to determine the effect of salary, incentives and work environment on job satisfaction of the cashier division of PT Tiptop Pondok Gede branch both passively and simultaneously using SPSS version 24. The population in this study was the cashier division employees, namely 40 respondents with sempel determination using the Saturated Sampling Technique with a total of 40 respondents. This study uses quantitative methods, namely by using primary data collection through distributing questionnaires to respondents. From the results of data analysis obtained, it shows that there is a positive and significant influence between the variables of Salary (X1), Incentives (X2) and Work Environment (X3) on Job Satisfaction (Y). This is proven by the X1 tcount value of 3.550 greater than the ttable of 2.0261 and a significant value of 0.001 (0.001 < 0.05) then the ) and the X3 tcount value of 2.734 greater than the ttable of 2.0261 and a significant value of 0.010 (0.010 < 0.05). From the analysis of this data shows that there is a joint (simultaneous) and significant influence between the variables of Salary (X1), Incentives (X2), Work Environment (X3) on Job Satisfaction (Y), which in this case is proven by the Fcount value of 61.331> Ftable 2.87, which is reinforced by a significant value of 0.000 < Ftable 0.05.